Cost-utility analysis of vasoconstrictors plus albumin in the treatment of thai patients with type 1 hepatorenal syndrome - Sermsiri Sangroongruangsri (2022)
Purpose: Type 1 hepatorenal syndrome (type 1 HRS) or hepatorenal syndrome-acute renal injury (HRS-AKI) leads to high short-term mortality rates in patients with cirrhosis. Vasoconstrictor therapy effectively improves survival of these patients and has been a bridge to liver transplantation. The aim of this study was to assess the cost-utility of terlipressin plus albumin (T+A) and noradrenaline plus albumin (N+A) compared to best supportive care (BSC) for treating type 1 HRS patients in Thailand. Methods: A cost-utility analysis using a six-state Markov model was performed from societal and payer perspectives over a lifetime horizon. The clinical outcomes, costs, and utility parameters were obtained from literature, network meta-analyses, and expert opinion. One-way and probabilistic sensitivity analyses were conducted to account for uncertainty. Results: The T+A yielded the highest cost (848,325 Thai Baht (THB)) and health outcomes (2.82 life-years (LY) and 2.27 quality-adjusted life-years (QALY)). Compared to BSC, incremental cost-effectiveness ratios (ICERs) of the T+A and N+A were 377,566 and 412,979 THB per QALY gained, respectively. If N+A is administered outside the intensive care unit, the ICER was 308,964 THB per QALY. The treatment cost after liver transplantation from year 3 onwards was the most influential factor for ICERs, followed by the cost of terlipressin, duration of noradrenaline treatment, and cost of albumin. At the Thai societal willingness-to-pay threshold of 160,000 THB per QALY gained, the probabilities of being cost-effective for T+A, N+A, and BSC were 11%, 20%, and 69%, respectively. Conclusion: The T+A and N+A treatments would not be cost-effective compared to BSC in the Thai setting.